REAL TIME IDENTIFICATION OF STAMPING DIES - RohitKorde; T.R.Vijayaram; SujitBarage; VivekMarathe (International Journal of Innovations in Engineering Research and Technology, 2021)
The work is concern with real timeidentification of stamping dies using RFID tags,readerand optical laser distance sensor. Dies are part of Press machine and made up of metal. Due to randomly placed large quantity of dies in certain area, identifying particular die is main problem.In this technology RFID technology used for identifying diesand optical laser distance sensor used for locating die position.Wire communication is not possible in this system so wireless communication (IEEE 803.11) standard used. For storing data MY SQL database used and for programming PHP language used. To make system more user-friendly android application also developed. RFID based asset trackinghelps improve security as well as efficiency. The improved security and efficiency results in a significant return on investment ina very short duration